Chemoradiotherapy for maxillary sinus adenoid cystic carcinoma using superselective intra‐arterial infusion via a superficial temporal artery. Issue 3 (26th September 2011) - Adachi, Makoto; Mitsudo, Kenji; Yamamoto, Noriyuki; Hagiwara, Sumitaka; Shigetomi, Toshio; Fujimoto, Yasushi; Lai, Stephen Y.; Tohnai, Iwai; Irish, Jonathan
Abstract Background The efficacy of concurrent intra‐arterial infusion chemoradiotherapy for adenoid cystic carcinoma (ACC) has been described in only a few reports. Herein, we report on 2 patients with unresectable ACC of the maxillary sinus treated with this approach. Methods Patients received concurrent chemoradiotherapy. External beam radiation was administered 5 times a week at 2 Gray (Gy) per fraction for a total of 60 Gy. Chemotherapy consisting of docetaxel and cisplatin was administered by superselective intra‐arterial infusion via a superficial temporal artery. Results After the completion of all treatments in both patients, biopsy specimens of the primary lesions showed complete disappearance of all viable and nonviable tumor cells and new bone formation at the bony walls of the maxillary sinus. Although complications such as mucositis, neutropenia, and anorexia were observed, they were well‐tolerated and manageable. Conclusion Concurrent chemoradiotherapy using superselective intra‐arterial infusion is a potential option for patients with unresectable maxillary ACC. © 2011 Wiley Periodicals, Inc. Head Neck, 2013